Modern Mouride Marabouts and their Young Disciples in Dakar - Kingsbury, Kate (Anthropologica, 2018)
This article provides an analysis of new religious Sufi Mouride movements in Senegal. In it, I analyse the charismatic leaders and their young disciples, elucidating that their interactive rapport forms the basis of the popularity of these movements. I demonstrate that young Dakarois have played a significant role in the regeneration of religious belief among the Mourides, and I posit that the leaders of these movements proffer a counter-discourse on leadership that provides an alternative to the gerontocratic models that characterise politics as well as traditional Mouride movements. I explain that the religious ontologies that new Mouride marabouts offer youth afford the latter the possibility to reconceptualise their identities, providing them with a modern pious paradigm that aligns with both their spiritual and physical needs.